Age polyethism in the leaf-cutting ant Acromyrmex subterraneus brunneus Forel, 1911 (Hym., Formicidae) - Camargo, R. S.; Forti, Luiz Carlos [UNESP]; Lopes, J. F. S.; Andrade, A. P. P.; Ottati, A. L. T. (Blackwell Publishing, 2007)
This study describes and quantifies the behavioural acts of two laboratory colonies of Acromyrmex subterraneus brunneus by investigating worker age polyethism. Twenty-nine behavioural acts were recorded during the 19-week observation period. Young individuals performed tasks inside the nest related to brood care and care for the fungus garden, whereas older individuals performed activities outside the nest such as foraging and activities in the waste chamber. The average longevity (+/- SD) was 108.21 +/- 3.30, 109.15 +/- 1.92 and 122.71 +/- 1.55 days for large, medium and small workers, respectively. The small-sized workers presented a higher probability of reaching older age than large- and medium-sized workers. This study describes task switching according to age polyethism and the relationship of physical and temporal subcastes.
Keywords: behavioural acts; leaf-cutting ants; temporal subcastes